2008
DOI: 10.1143/jpsjs.77sc.61
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Pseudogap Features Observed in Iron Oxypnictide Superconductors

Abstract: We present angle-integrated photoemission spectroscopy (PES) study of LaOFeAs:F (Tc = 26 K) and LaOFeP:F (Tc = 5 K) using He I line (hν = 21.2 eV) and laser (hν = 6.994 eV) as excitation light sources. We find quantitatively consistent results between the He I and the laser PES measurements: LaFeAsO:F exhibits a temperature-dependent pseudogap as large as ∼0.1 eV at 300 K, whereas LaFePO:F exhibits a ∼20-meV pseudogap. We discuss possible origin of the T -dependent pseudogap specifically observed in LaFeAsO:F … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Synchrotron-based ARPES thus show that SC gap in AsP122 is smaller than PG, consistent with laser-ARPES. PG with an energy scale higher than SC gap has been also reported for a variety of iron-based superconductors by several experimental probes [32,33,35,36,39,40].…”
Section: Asp122 System Shows Quasi-two Dimensionalmentioning
confidence: 56%
See 1 more Smart Citation
“…Synchrotron-based ARPES thus show that SC gap in AsP122 is smaller than PG, consistent with laser-ARPES. PG with an energy scale higher than SC gap has been also reported for a variety of iron-based superconductors by several experimental probes [32,33,35,36,39,40].…”
Section: Asp122 System Shows Quasi-two Dimensionalmentioning
confidence: 56%
“…Although several studies have been reported on the PG formation [32][33][34][35][36][37][38][39][40], the PG phase has not been completely established in the phase-diagrams of the iron-pnictides. In particular, only one angle-resolved photoemission spectroscopy (ARPES) study has shown the presence of a normal state energy gap in momentum space for Ba 0.75 K 0.25 Fe 2 As 2 [41].…”
mentioning
confidence: 99%
“…For instance, FeSe on SrTiO 3 (001) has a gap as large as 18meV 32,33 . Gap sizes up to 20 meV have also been reported in LaFeAsO and LaFePO 34 .…”
Section: Discussionmentioning
confidence: 81%
“…Thus it would be most desirable to reproduce similar experiments on superconducting substrates with large gap sizes as realized in some of the high-temperature superconductors. For example, the Re(0001)-O(2×1) substrate has a gap size of 280-330 µeV 24 whereas superconducting gaps of up to 20 meV have been reported in monolayer FeSe 32,33 and also up to 20 meV in LaFeAsO and LaFePO 34 . Obvious candidates are the high T c cuprate and iron-based superconductors as substrates for Shiba systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other issues to be resolved are confirmation of pseudo-gaps [90][91][92][93][94][95][96][97][98][99][100][101], finding the relationship between pseudo-gaps and superconductivity, finding the origin of the T c enhancement in FeSe monolayer grown on SrTiO 3 substrate [34,[107][108][109][110][111], confirmations of quantum critical points [101][102][103][104][105][106], material and doping dependence of orbital order, electronic structure studies of 1111 systems [35]. Information on these issues could provide clues to the microscopic mechanism.…”
Section: Unresolved Issues and Further Studiesmentioning
confidence: 99%